Performance study of DVB-T2 digital broadcasting system over fading channels - Xu, Guangyou (Nanyang Technological University, 2023)
This dissertation begins with an introduction of DVB-T2 standard and system. Then there is a discussion about the key technologies adopted in DVB-T2. For better understanding of DVB-T2 simulation, some classical fading channels and simulation scenarios are introduced as well. The simulation part consists of sim ulation system and parameter setting, simulation results and analysis. It can be concluded that DVB-T2 system has better performance when there is a direct path for signal transmission. 256QAM and 64QAM are recommended in fixed and portable reception situations, respectively. The constellation rotation tech nique is also effective and recommended for the scenarios without direct paths.